2018
DOI: 10.1007/s40520-018-0949-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of diagnostic accuracy of Fagan’s two-step nomogram in increasing the value of predictive tools for prostate cancer: application of specific spatial distribution of positive/negative bioptic cores to predict extracapsular extension

Abstract: This pioneering study may justify the use of the above nomogram in testing "local" predictive parameters in combination with pre-existing nomograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The primary aim of the study was to test the improvement in the prediction of ECE-according to Partin Tables given a particular condition at prostate biopsy (pericapsular cores uninvolved by PCa). In conclusion, authors found that the post-test probability of having ECE-when all lateral cores (ie pericapsular cores) were negative was 14.1%, with a substantial gain of 7.5% as compared to Partin estimates for ECE-(21.6%) [18].…”
Section: Clinical Use Of Fagan's Two-step Nomogrammentioning
confidence: 78%
See 1 more Smart Citation
“…The primary aim of the study was to test the improvement in the prediction of ECE-according to Partin Tables given a particular condition at prostate biopsy (pericapsular cores uninvolved by PCa). In conclusion, authors found that the post-test probability of having ECE-when all lateral cores (ie pericapsular cores) were negative was 14.1%, with a substantial gain of 7.5% as compared to Partin estimates for ECE-(21.6%) [18].…”
Section: Clinical Use Of Fagan's Two-step Nomogrammentioning
confidence: 78%
“…Another way to address the same issue requires to focus on statistics, as in Dal Moro et al which resumed an old-fashioned but user-friendly graphic calculator (Fagan's two-step nomogram) to predict the risk of ECE+ vs ECE-at radical prostatectomy, given the number of positive lateral cores at biopsy [18].…”
Section: Clinical Use Of Fagan's Two-step Nomogrammentioning
confidence: 99%
“…The forest plots of validation cohorts for MRI-inclusive and clinical nomograms are presented in Supplementary Figures S1 - S4 . In the subgroup analysis, eight external validations of the Partin table [ 50 , 51 , 53 55 , 59 , 61 , 62 ] showed a pooled AUC of 0.72(95% CI: 0.68, 0.76), and 5 external validations of the MSKCC nomogram [ 55 , 58 , 60 62 ] showed a pooled AUC of 0.79(95% CI: 0.75, 0.82).…”
Section: Resultsmentioning
confidence: 99%
“…The bivariate effect model was used to combine statistics such as SEN, SPE, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) with 95% confidence intervals (CIs), plot summary receiver operating characteristic (SROC) curve, and to calculate the value of area under the curve (AUC). Fagan's nomogram was used to evaluate the a priori probability and a posteriori probability of PET / CT in distinguishing the two tumors ( 12 ). A sensitivity analysis was used to evaluate the stability of the results, and the Deek's test was used to judge the presence of bias in the study ( 13 ).…”
Section: Methodsmentioning
confidence: 99%